Practical Issues Regarding International Underppinnings of Tax Legislation Under the Auspices of Law No. 296/2020 - Dumiter, Florin Cornel; Jimon, Ștefania Amalia (Journal of Legal Studies, 2021)
In this article, it will be analyzed, from the perspective of doctrine and jurisprudence, the implications of some international aspects of tax legislation, under the auspices of the latest changes in the field of taxation made by Romania. For this purpose, it will be analyzed the implications of the new fiscal provisions regarding the international aspects from the perspective of Law no. 296/2020. In this sense, it will be focused upon certain issues such as international double taxation, transfer prices, affiliated businesses and corporate tax. Also, the case presented in the jurisprudence section enriched in the second part of the article comes to support the framework of the future application of the new provisions regarding certain fiscal aspects with elements of foreignness in Romania. The results of the research subsumed in this article highlight the fact that the tax legislation in Romania has had a significant improvement, especially in terms of international aspects of financial and tax law. In conclusion, both the analysis of the evolution of tax legislation and the case law presented show that there are significant improvements at a national level, both in terms of the quality of the enactment of a tax law and the way in which the provisions of the law are implemented in practice.